Are emotions perceptions of value (and why this matters)? A review essay of Christine Tappolet's Emotions, Values, and Agency. (19th May 2018) - Kurth, Charlie; Crosby, Haley; Basse, Jack
Abstract: In Emotions, Values, and Agency, Christine Tappolet develops a sophisticated, perceptual theory of emotions and their role in wide range of issues in value theory and epistemology. In this paper, we raise three worries about Tappolet's proposal.